Molecular aspects of antitumor effects of a new platinum(IV) drug - Kaspárková, Jana; Nováková, Olga; Vrána, Oldrich; Intini, Francesco; Natile, Giovanni; Brabec, Viktor (Molecular pharmacology, 2006)
The new platinum(IV) complex cis,trans,cis-[PtCl(2)(CH(3)COO)(2)-(NH(3))(1-adamantylamine)] [adamplatin(IV)] seems promising for the perspective application in therapy of corresponding tumors. It is therefore of great interest to understand details of mechanisms underlying its biological efficacy. Cellular uptake of the drug, alterations in the target DNA induced by platinum drugs along with processing of platinum-induced damage to DNA and drug inactivation by sulfur-containing compounds belong to major pharmacological factors affecting antitumor effects of platinum compounds. We examined in the present work the significance of these factors in the mechanism of antitumor effects of adamplatin(IV) and compared the results with those of the parallel studies performed with "conventional" cisplatin. The results show that deactivation of adamplatin(IV) by sulfur-containing compounds (such as glutathione or metallothioneins) is likely to play a less significant role in the mechanism of resistance of tumor cells to adamplatin(IV) in contrast to the role of these reactions in the effects of cisplatin. Moreover, the treatment of tumor cells with adamplatin(IV) does not result in DNA modifications that would be markedly different from those produced by cisplatin. In contrast, the effects of other factors, such as enhanced accumulation of the drug in cells, strong inhibition of DNA polymerization by these adducts, lowered DNA repair, and DNA-protein cross-linking are different from the effects of these factors in the mechanism underlying activity of cisplatin. Hence, the differences between effects of adamplatin(IV) and cisplatin observed in the present work on molecular level may help understand the unique activity of adamplatin(IV).
Keywords: Ascorbic Acid; oprava DNA; Animals; HeLa Cells; Platinum; platina; Base Sequence; Cell-Free System; Cell Line, Tumor; Viral Proteins; bezbuněčný systém; Neoplasms; nádory; DNA; HIV-1; HeLa buňky; lidé; Molecular Sequence Data; adukty DNA; Antineoplastic Agents; RNA-Directed DNA Polymerase; protinádorové látky; Sulfur Compounds; DNA Repair; Cross-Linking Reagents; Adamantane; organoplatinové sloučeniny; reagencia zkříženě vázaná; molekulární sekvence - údaje; plazmidy; DNA Adducts; DNA-Directed RNA Polymerases; kyselina askorbová; sekvence nukleotidů; virové proteiny; DNA řízené RNA-polymerasy; High Mobility Group Proteins; krysa rodu Rattus; adamantan; Organoplatinum Compounds; Plasmids; proteiny s vysokou pohyblivostí; zvířata; sloučeniny síry; Rats; reverzní transkriptasa; nádorové buněčné linie; Humans